2019
DOI: 10.3390/buildings9050131
|View full text |Cite
|
Sign up to set email alerts
|

Minimising the Deviation between Predicted and Actual Building Performance via Use of Neural Networks and BIM

Abstract: Building energy performance tools are widely used to simulate the expected energy consumption of a given building during the operation phase of its life cycle. Deviations between predicted and actual energy consumptions have however been reported as a major limiting factor to the tools adopted in the literature. A significant reason highlighted as greatly influencing the difference in energy performance is related to the occupant behaviour of the building. To enhance the effectiveness of building energy perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Moreover, from a detailed survey, one review [41] study offers model categorization in terms of whether the developed model is based on data, and therefore the authors categorized wide-ranging behavior models into data-driven and simulation-based approaches. In brief, modeling using data-driven methods involves an extensive amount of data to build a statistical model for selected occupant behaviors, although simulation-based energy models depend on empirical or pre-defined rules that control the occupant behavior configuration [44,45]. A comprehensive list of quantitative modeling for this review study is shown in Table 1.…”
Section: Classification Of Occupant Behavior Modelingmentioning
confidence: 99%
“…Moreover, from a detailed survey, one review [41] study offers model categorization in terms of whether the developed model is based on data, and therefore the authors categorized wide-ranging behavior models into data-driven and simulation-based approaches. In brief, modeling using data-driven methods involves an extensive amount of data to build a statistical model for selected occupant behaviors, although simulation-based energy models depend on empirical or pre-defined rules that control the occupant behavior configuration [44,45]. A comprehensive list of quantitative modeling for this review study is shown in Table 1.…”
Section: Classification Of Occupant Behavior Modelingmentioning
confidence: 99%
“…This process involves a single simulation for all of a home's occupants (instead of a separate one for each user profile), thus minimising HVAC (heating, ventilation and air conditioning) consumption prediction errors. Processes that use ANNs are 72% more accurate than traditional static methods [29]. The forecasting process discussed in [29] was based on three steps: (1) input data related to the building and users collected from IoT sensors was recorded in the BIM model, (2) ANN-based AI statistical data was used to perform a simulation, and (3) the results were compared to reality to obtain new input data if those results were positive.…”
Section: Related Workmentioning
confidence: 99%
“…Processes that use ANNs are 72% more accurate than traditional static methods [29]. The forecasting process discussed in [29] was based on three steps: (1) input data related to the building and users collected from IoT sensors was recorded in the BIM model, (2) ANN-based AI statistical data was used to perform a simulation, and (3) the results were compared to reality to obtain new input data if those results were positive. Furthermore, existing monitoring approaches are usually simplistic and inappropriate in the way that they try to define then regulate a building's cooling and/or heating based on a fixed indoor temperature.…”
Section: Related Workmentioning
confidence: 99%
“…In order to construct the next generation of occupancy models that can reliably anticipate occupants' behavior, new DL approaches are being employed. Hammad (Hammad, 2019) presented a strategy for reducing the difference between expected and real energy consumption rates by merging BIM with an ANN model. A deep neural network training to predict occupant behavior results in accurate BIM representations, further confirmed by energy simulations.…”
Section: Detection and Prediction Of Occupancy And Energy Managementmentioning
confidence: 99%